Presidentas municipales en México: acoso y violencia política (2010-2016) - Barrera Bassols, Dalia (2016)
This article presents the results of an investigation concerning political harassment and violence towards female mayors in Mexico. It also aims to paint a picture of the social and political background of these phenomena in the context of authoritarian, clientelistic and male chauvinistic politics, which is told through the testimonies of female mayors collected from 1996 until 2009. Violence against mayors of both genders in Mexico starts with the so called war on drugs –a policy adopted in 2006 by the Federal government- which generates denouncements and proposals from political parties and municipalist associations, as well as manifestations of worry of deputies and senators. The climate of generalized violence in the country reached a critical state in January of 2016 with the assassination of the mayor of Temixco –in the state ofMorelos-Gisela Mota Ocampo, the first female mayor to be assasssinated by an armed comando.The present article synthesizes the results of an hemerographic tracing while presenting some of the most representative cases of political harassment and violence against female mayors in Mexico from 2010 until January of 2016, when said assassination took place.